Outcome of nanofluid flow containing arbitrary shape nanoparticles induced by a permeable stretching sheet - Kundu, Prabir Kumar; Sarkar, Amit (Zielona Góra: Uniwersytet Zielonogórski)
In this work we have discussed the impact of thermal radiation on heat transfer to nanofluid flow over an unsteady permeable stretching sheet using various types of arbitrary shape nanoparticles of Copper (Cu), Silver (Ag), Alumina (Al2O3), and Titania Oxide (TiO2) in the base fluid. Suitable transformations have been employed to build ODEs from the partial differential equations.
Keywords: nanofluid; heat transfer; boundary layer flow; thermal radiation; permeable stretching sheet